"Forgive us our debts": Jubilee prays the Lord's Prayer. (November 2021) - Swancutt, Diana M.
The Lord's Prayer has long held a venerable place in the life of the church. This article argues that one of the reasons for this central importance is that the Lord's Prayer was a habitus -forming reminder to Jesus's followers to enact Jubilee daily as the defining socio-eschatological praxis of early Christian communities. This interpretation tempers the tendency to spiritualize ancient readings of the Lord's Prayer with the steel of collective social practice, the physicality of the body, and the grit of social need.